2021
DOI: 10.1111/ppl.13314
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous methyl jasmonate promotes salt stress‐induced growth inhibition and prioritizes defense response of Nitraria tangutorum Bobr.

Abstract: Jasmonates (JAs) play a key role in the regulation of growth and the defense response to environmental stresses. JAs inhibit plant growth and promote defense response. However, their roles in desert halophyte in the response to salt stress remain poorly understood. The effects of the combination of methyl jasmonate (MeJA) and NaCl treatment (the "MeN" condition) on the growth regulation and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 67 publications
1
15
1
Order By: Relevance
“…It was observed that IBU can partially rescue the wound-induced decrease of growth, indicating that the wound-induced growth degradation is associated with the JA biosynthesis. This observation is consistent with the previous reports that exogenous JA can suppress the plant growth and repeated wounding had less effect on the growth of the mutant that is unable to synthesize JA, compared to the wild type plants [ 31 , 50 ]. We also noted that MYC mutation partially rescued the wound-induced decrease of leaf area and root length but had no significant effects on fresh and dry weight of the wounded seedlings.…”
Section: Discussionsupporting
confidence: 93%
“…It was observed that IBU can partially rescue the wound-induced decrease of growth, indicating that the wound-induced growth degradation is associated with the JA biosynthesis. This observation is consistent with the previous reports that exogenous JA can suppress the plant growth and repeated wounding had less effect on the growth of the mutant that is unable to synthesize JA, compared to the wild type plants [ 31 , 50 ]. We also noted that MYC mutation partially rescued the wound-induced decrease of leaf area and root length but had no significant effects on fresh and dry weight of the wounded seedlings.…”
Section: Discussionsupporting
confidence: 93%
“…Low-medium salt in parachinar local and all concentrations of salt in swat-84 reduced the shoot growth parameters alone and in combination with the exogenous foliar-JA application. In a recent study, it was demonstrated that exogenous MeJA inhibited the growth of seedlings of Nitraria tangutorum, resulting in shorter shoots, smaller internodes, and lower fresh weight [47]. Plants that are exposed to environmental stresses experience growth-defense tradeoffs, and JA is thought to be a key factor in these tradeoffs [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…However, the combination of salinity and MeJA intensified plant growth inhibition and senescence [143]. Exogenous MeJA amplified salt stress-induced growth inhibition and prioritized defensive responses (e.g., antioxidant defense, osmotic adjustment, and ion homeostasis) in Nitraria tangutorum [144].…”
Section: Salt Stressmentioning
confidence: 99%